Risk Factors for Type 2 Diabetes Mellitus in Adolescents from a Doctor's Office - Marlene Ferrer Arrocha; Elikana Kiplagat Chirchir; Maylín Isabel Alonso Martínez; Héctor Pérez Assef (Revista Finlay)
Background: type 2 diabetes mellitus in pediatric ages has become a health problem, related to the increased prevalence of obesity. Objective: to identify the risk factors for the development of type 2 diabetes mellitus in adolescents from a doctor's office at the Héroes de Girón Teaching Polyclinic in the Havana’s Cerro municipality. Methods: a descriptive cross-sectional study was carried out that included apparently healthy adolescents, who belonged to the clinic # 9 of the Héroes de Girón Teaching Polyclinic in the Cerro municipality in Havana. The variables studied were: age, sex, personal and family history of diabetes mellitus, weight, height, waist circumference, body mass index, blood pressure, presence of central obesity and waist/height ratio, consumption of fruits and vegetables, and physical activity. A questionnaire based on the modified Finish Diabetes Risk Score scale for children and adolescents was applied. Results: 70 adolescents were studied, with a mean age of 16.6 years. A high frequency of overweight and obesity was detected. 31.4 % were prehypertensive and 5.7 % hypertensive. The risk scale showed that 64.3 % had a moderate risk with predominance in the female sex. Conclusions: the Finish Diabetes Risk Score can be a useful instrument in the identification of adolescents at risk for diabetes in Primary Health Care. The high frequency of adolescents at risk of developing diabetes alerts us to the need to draw up prevention strategies to avoid the development of the disease and its consequences in later stages of life.